Pengembangan Bahan Ajar Mikrobiologi Pangan Berbasis Masalah - Harahap, Sri Rahmadani; Harahap, Fauziyah; Hasruddin, Hasruddin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
The research aims to: (1) Develop a textbook of microbiological food at based problem; (2) determine the response of microbiology lecturer and students to textbooks developed. The textbook was developed to be used as a guide students in conducting lectures learning in the classroom. Data on the quality of development product were collected by questionnaire/questionnaire. Textbook was developed by using a development model Thiagarajan (4-D) that has been modified into a 3-D. The results showed: (1) Validation team of material experts showed an average of 88% (the excellent category); (2) Validation of the expert team of instructional design showed an average 95% (excellent category); (3) Ratings lecturer of microbiology showed an average of Â 92% (a very interesting category); (4) Trial individuals showed an average 89% (a very interesting category); (5) Trial small group showed an average of 84% (a very interesting category); (6) a finite field trial group showed an average of 87% (a very interesting category).So it can be concluded that product development research microbiology textbooks of based prombles that development is feasible to be used as a textbook students at third semester of Biology Education PPs of Unimed or as supporting lecture material on the material Applied Microbiology in Food Microbiology at Unimed.